2012
DOI: 10.1210/jc.2012-1170
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Capacity of the Parathyroid Glands after Total Thyroidectomy in Normocalcemic Subjects

Abstract: In thyroidectomized patients, normal postoperative calcium and PTH values do not exclude a reduced secretory response of the parathyroids to hypocalcemic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…Another explanation for the lower PTH levels and presumably higher cortical thickness might relate to distorted parathyroid function following thyroidectomy. Lower PTH levels in premenopausal patients with DTC have also been reported in other studies . Given that higher cortical thickness at the radius has been reported in patients with hypoparathyroidism, it is possible that higher cortical thickness is related to the ‘relative hypoparathyroidism’ observed in this group.…”
Section: Discussionsupporting
confidence: 80%
“…Another explanation for the lower PTH levels and presumably higher cortical thickness might relate to distorted parathyroid function following thyroidectomy. Lower PTH levels in premenopausal patients with DTC have also been reported in other studies . Given that higher cortical thickness at the radius has been reported in patients with hypoparathyroidism, it is possible that higher cortical thickness is related to the ‘relative hypoparathyroidism’ observed in this group.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, even though most patients recover from parathyroid failure after TT, the secretory capacity of the parathyroid glands is left impaired. This is in agreement with the seminal 1965 contribution of Wade et al (19) and other recent observations (16,20). This relationship between intraoperative surgical injury of the parathyroid glands and reduced iPTH reserve has been further confirmed in the study of Lang et al (21) who found that after TT for benign disease, PGRIS was the major determinant of protracted hypoparathyroidism and that aggressive parathyroid identification resulted in more patients developing postoperative hypocalcemia and protracted hypoparathyroidism.…”
Section: Sitges-serra Et Al Likelihood Of Permanent Postoperative Hysupporting
confidence: 87%
“…Moreover, it is not always evident which is the best way to monitor postoperative function of the gland [8]. The number of available provocative tests for the evaluation of the parathyroid function is limited to EDTA infusion test, sodium citrate infusion test, and, recently, sodium bicarbonate infusion test [37]. We have chosen to employ this last test for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium bicarbonate test was performed as previously described [6, 7]. The volunteers were in fasting state for at least 4 hours and 35 mL/m 2 of body surface of 8.4% sodium bicarbonate solution was infused in one arm over 2 minutes and blood samples for the determination of serum PTH were drawn before (PTH 0 ) and at 3 (PTH 3 min ), 5 (PTH 5 min ), 10 (PTH 10 min ), 30 (PTH 30 min ), and 60 minutes (PTH 60 min ) after the infusion of the other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation